Metabotropic glutamate receptors in GtoPdb v.2021.3. (2021) - Acher, Francine; Battaglia, Giuseppe; Bräuner-Osborne, Hans; Conn, P. Jeffrey; Duvoisin, Robert; Ferraguti, Francesco; Flor, Peter J.; Goudet, Cyril; Gregory, Karen J.; Hampson, David; Johnson, Michael P.; Kubo, Yoshihiro; et al.
No abstract available